2006
DOI: 10.1007/s10461-006-9118-2
|View full text |Cite
|
Sign up to set email alerts
|

How Uganda Reversed Its HIV Epidemic

Abstract: Uganda is one of only two countries in the world that has successfully reversed the course of its HIV epidemic. There remains much controversy about how Uganda's HIV prevalence declined in the 1990s. This article describes the prevention programs and activities that were implemented in Uganda during critical years in its HIV epidemic, 1987 to 1994. Multiple resources were aggregated to fuel HV pre-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
57
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 7 publications
0
57
0
Order By: Relevance
“…The first successful examples of behavior change that led to decreased HIV transmission incidence were reported in men who have sex with men (MSM) (Winkelstein et al 1988;Kippax and Race 2003). Subsequently, a number of countries have attributed decreases in HIV incidence to changes in sexual behavior, including Brazil, Cote d'Ivoire, Kenya, Uganda, Malawi, Tanzania, Zimbabwe, Burkino Faso, Namibia, and Swaziland (Stoneburner and Low-Beer 2004;Slutkin et al 2006). …”
Section: Behavioral Strategiesmentioning
confidence: 99%
“…The first successful examples of behavior change that led to decreased HIV transmission incidence were reported in men who have sex with men (MSM) (Winkelstein et al 1988;Kippax and Race 2003). Subsequently, a number of countries have attributed decreases in HIV incidence to changes in sexual behavior, including Brazil, Cote d'Ivoire, Kenya, Uganda, Malawi, Tanzania, Zimbabwe, Burkino Faso, Namibia, and Swaziland (Stoneburner and Low-Beer 2004;Slutkin et al 2006). …”
Section: Behavioral Strategiesmentioning
confidence: 99%
“…Although the prevalence of HIV infection among adults aged 15-49 years in Uganda decreased from 18.3% in 1992 to 6.7% in 2005, acquired immunodeficiency syndrome (AIDS) continues to be the leading cause of death among adults in Uganda (1)(2)(3)(4). The majority of deaths due to HIV/AIDS occur in the age-group that has the highest expectations for labour output and care-giving, and the loss of these household members has significant negative impact on the socioeconomic, nutritional and health status of affected households, their extended families, and their communities.…”
Section: Introductionmentioning
confidence: 99%
“…As Slutkin et al ( 2006) emphasize, the observed behavior change should not be attributed to one behavior change component or another, but rather to the intensity and breadth of the health education campaign, as illustrated by its deep extension into communities and strong financial support. The prevention success of Uganda is thus attributable to the provision of full information about all means of transmission and protection by many sectors of society, along with efforts to destigmatize HIV/AIDS by being open about the disease, showing compassion and providing care to those who are infected and affected.…”
mentioning
confidence: 99%